The The Development of Biometric Sensors to Net Sports Volleyball (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The objective of this research is to design biometric sensor designs for the net of volleyball to detect failures occurring on the net. The approach used in this research is Research and Development (R & D) method. Research subjects were athletes and volleyball referees. Expert volleyball volleyball results one is better with the total score of 85, the validation of the volleyball of two is good with the number of score 87, for the electro expert one expressed well with the total score of 86, the two electro experts stated both with the number of scores 88. The conclusion of this study Produces a net biometric sensor product for the net of volleyball in 2017 in a volley ball beast worthy of use in a volleyball match, for athletes referees and coaches may recommend trying as a means of detecting errors occurring on the net of the volleyball.